2016
DOI: 10.1186/s13071-016-1780-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of fascioliasis, toxocariasis, strongyloidiasis and cysticercosis in blood samples diagnosed in Medic Medical Center Laboratory, Ho Chi Minh City, Vietnam in 2012

Abstract: BackgroundDespite the global effort against neglected tropical diseases (NTDs), developing countries with middle to low income are still burdened by them. Vietnam has been undergoing substantial economic growth and urbanization, but underprivileged people living in rural and suburban areas are still having little access to public health infrastructure and proper sanitation. Hitherto, limited information is available for seroprevalence and risk factors of several parasitic diseases in Vietnam.MethodsA retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 26 publications
7
37
1
1
Order By: Relevance
“…This result is in concordance with the report from Luvira and coworkers [ 48 ]. In contrast to our results, [ 49 51 ] there have been reported correlations between antibody levels and age, sex or lpg. This discrepancy maybe due to the insufficient numbers of samples examined in our study or due to the restricted range of sampling in the endemic area.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in concordance with the report from Luvira and coworkers [ 48 ]. In contrast to our results, [ 49 51 ] there have been reported correlations between antibody levels and age, sex or lpg. This discrepancy maybe due to the insufficient numbers of samples examined in our study or due to the restricted range of sampling in the endemic area.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, ELISA-based testing samples from a reference laboratory in Ho Chi Minh City, Vietnam, revealed that roughly half of individuals had been exposed to more than one parasite. 22 Eosinophilia was the likely reason for Strongyloides testing, which was present either alone or in combination with additional symptoms in 88% of our seropositive patients. The presence of eosinophilia among those who were seropositive was comparable with data reported elsewhere.…”
Section: Discussionmentioning
confidence: 79%
“…This may be because the vegetables and roots that are cooked together with the pork are contaminated with tapeworm eggs from the soil around the cooking site. (28) Consumption of raw or halfcooked T. solium larvae-containing pork is an indirect factor, since it causes taeniasis, which results in contamination of the environment with T.solium eggs, but causes cysticercosis upon autoinfection. This is supported by the study of Khaing et al (23) who reported that the risk factors of cysticercosis transmission are among others community cooking resulting in consumption of half-cooked or raw meat.…”
Section: Discussionmentioning
confidence: 99%